Cognitive Impairment and Its Associated Factors in Older Adults Living in High and Low Altitude Areas: A Comparative Study - Liu, Shou; Wang, Fei; Zhang, Cheng; Zhang, Qinge; Dang, Zhan-Cui; Ng, Chee H.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2022)
Background: Cognitive impairment is a major health concern in older adults. Few studies examined the association between environmental factors and cognitive impairment, especially in high altitude areas. We compared the prevalence of cognitive impairment between older adults living in high altitude and low altitude areas. Methods: This is a cross-sectional, comparative study of older adults conducted at Qinghai (high altitude group), and Guangzhou (low altitude group). Cognition, depressive symptoms and quality of life (QOL) were measured using standardized instruments. Results: Altogether, 644 older adults (207 in Qinghai and 437 in Guangzhou) completed the assessment. The prevalence of cognitive impairment in older adults living in the high altitude area was 94.7% (95% CI: 91.6%-97.7%), while the corresponding figure was 89.2% in the low altitude area (95% CI: 86.3%-92.1%). After controlling for covariates, the high altitude group appeared more likely to have cognitive impairment (OR=2.92, 95% CI: 1.23-6.91, P=0.015) compared to the low altitude group. Within the high altitude group sample, multinomial logistic regression analysis revealed that older age (aged 74 and above) was significantly associated with increased risk of severe cognitive impairment (OR=3.58, 95%CI:1.44-8.93, P=0.006), while higher education level (secondary school and above) was associated with decreased risk of moderate cognitive impairment (OR=0.43, 95%CI: 0.22-0.85, P=0.006). After controlling for covariates, QOL did not differ significantly across physical (F(1,207)=1.83, P=0.163), psychological (F(1,207)=1.50, P=0.225), social (F(1,207)=2.22, P=0.111) and environmental domains (F(1,207)=0.49, P=0.614) between normal/mild, moderate and severe cognitive impairment subgroups within the high altitude group. Conclusion: This study found that cognitive impairment was common among older adults, particularly those living in the high altitude area. Considering the negative impact of cognitive impairment on daily life, regular screening and appropriate interventions should be provided to older adults in need.